2D Organic–Inorganic Hybrid Thin Films for Flexible UV–Visible Photodetectors. (13th February 2017) - Velusamy, Dhinesh Babu; Haque, Md. Azimul; Parida, Manas R.; Zhang, Fan; Wu, Tom; Mohammed, Omar F.; Alshareef, Husam N.
Abstract : Flexible 2D inorganic MoS2 and organic g‐C3 N4 hybrid thin film photodetectors with tunable composition and photodetection properties are developed using simple solution processing. The hybrid films fabricated on paper substrate show broadband photodetection suitable for both UV and visible light with good responsivity, detectivity, and reliable and rapid photoswitching characteristics comparable to monolayer devices. This excellent performance is retained even after the films are severely deformed at a bending radius of ≈2 mm for hundreds of cycles. The detailed charge transfer and separation processes at the interface between the 2D materials in the hybrid films are confirmed by femtosecond transient absorption spectroscopy with broadband capability. Abstract : Flexible 2D inorganic MoS2 and organic g‐C3 N4 hybrid thin film photodetectors with tunable composition and photodetection properties are developed. The 5:5 hybrid films show broadband photodetection suitable for both UV and visible light with good responsivity, detectivity, and rapid photoswitching characteristics. The charge transfer processes at the interface of hybrid films are confirmed by femtosecond transient absorption spectroscopy.